2019
DOI: 10.1177/0300060519857021
|View full text |Cite
|
Sign up to set email alerts
|

Association of hemoglobin with incidence of in-hospital cardiac arrest in patients with acute coronary syndrome complicated by cardiogenic shock

Abstract: Objective This study was performed to investigate the association of the admission hemoglobin level with the incidence of in-hospital cardiac arrest (IHCA) in patients with acute coronary syndrome (ACS) complicated by cardiogenic shock (CS). Methods In this retrospective study, we reviewed the medical records of consecutive patients with ACS complicated by CS admitted to the coronary care unit from January 2014 to October 2017. Logistic regression models were carried out to evaluate the association between hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…A study reported significantly higher incidence of CS among mild and severe electrolyte decline groups while reduction in electrolytes is also indicated to early demise as compared to normal [ 22 ]. Higher haemoglobin levels have been suggested as protective factor among acute cardiac syndrome patients having complications of CS is also in agreement with the findings of present study [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…A study reported significantly higher incidence of CS among mild and severe electrolyte decline groups while reduction in electrolytes is also indicated to early demise as compared to normal [ 22 ]. Higher haemoglobin levels have been suggested as protective factor among acute cardiac syndrome patients having complications of CS is also in agreement with the findings of present study [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The association of hemoglobin levels and the risk of in-hospital cardiac arrest was elucidated upon by a number of studies. The multivariate analysis of a retrospective study of 211 consecutive patients with CS-AMI showed hemoglobin concentration under 112 g/L as an independent strong predictor of in-hospital cardiac arrest; in contrast, a 1-g/L increase in the hemoglobin levels indicated a 2.9% lower risk [ 42 ]. Therefore, the monitoring of hemoglobin levels could facilitate an early decision process.…”
Section: Resultsmentioning
confidence: 99%
“…The question is if this association is higher in younger patients. Underlying pathophysiological mechanisms were summarized by Xu et al Patients with anemia are more likely to develop ventricular arrhythmias, anemia induces tissue hypoxia in the ischemic regions and increases myocardial workload [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among patients with ACS, studies have shown that lower hemoglobin levels on admission are an independent predictor of increased risk for short-term mortality, more so if complicated with comorbidities of hypertension or chronic renal disease ( 14 , 15 ). When complicated with CS, a higher hemoglobin concentration is a protective factor for the development of in-hospital cardiac arrest ( 16 ). Lastly, cardiac arrest patients with a prolonged CPR duration were observed to be associated with a poorer prognosis ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%